2016
DOI: 10.1039/c5nr06690e
|View full text |Cite
|
Sign up to set email alerts
|

Confinement induced ordering in dewetting of ultra-thin polymer bilayers on nanopatterned substrates

Abstract: We report the dewetting of a thin bilayer of polystyrene (PS) and poly(methylmethacrylate) (PMMA) on a topographically patterned nonwettable substrate comprising an array of pillars, arranged in a square lattice. With a gradual increase in the concentration of the PMMA solution (Cn-PMMA), the morphology of the bottom layer changes to: (1) an aligned array of spin dewetted droplets arranged along substrate grooves at very low Cn-PMMA; (2) an interconnected network of threads surrounding each pillar at intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 84 publications
0
32
0
Order By: Relevance
“…Apart from thermal annealing 5 10 , solvent vapor exposure 63 , or quenching the film in a mix of solvent and non-solvent 64 , which are the commonly adopted approaches for engendering instability in a thin polymer film, a novel approach is to achieve dewetting during spin coating itself 65 69 . The method relies on the rupture of an extremely dilute solution layer on the substrate during spin coating itself, forming isolated solute patches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from thermal annealing 5 10 , solvent vapor exposure 63 , or quenching the film in a mix of solvent and non-solvent 64 , which are the commonly adopted approaches for engendering instability in a thin polymer film, a novel approach is to achieve dewetting during spin coating itself 65 69 . The method relies on the rupture of an extremely dilute solution layer on the substrate during spin coating itself, forming isolated solute patches.…”
Section: Introductionmentioning
confidence: 99%
“…While spin dewetting is totally undesired from the stand point of achieving a continuous thin film, it is finding potential utilization as a rapid meso fabrication technique for solution processable materials. Spin dewetting has already been utilized for fabricating array of polymers (PS and PMMA) droplets on topographically patterned substrate 65 69 . Very recently by Bandyopadhyay et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dewetting of thin liquid films (∼1-100 nm) on substrates with tailored heterogeneity has been recognized as a promising strategy for templating and nanopatterning. [1][2][3][4][5] When thin liquid films dewet physically or chemically patterned substrates, their dewetting mechanisms are more complex, as additional length scales pertaining to the pattern geometry need to be accommodated. This will also result in accelerated instability growth, [6][7][8][9][10] complex film morphologies, and/or different rupture locations, if any.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The template-directed and template-assisted dewetting of the thin polymer bilayer have been investigated extensively due to their technological and scientic importance. [31][32][33][34][35] Mukherjee et al 32,33 reported the dewetting process of a thin bilayer of polystyrene and poly(methylmethacrylate) on a topographically patterned nonwettable substrate, and using this method they fabricate many different structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [10][11][12][13][14][31][32][33][34][35] on the template-directed or template-assisted dewetting of the thin polymer lms mainly focus on the inuence of the geometry and size of the template pattern on the dewetting structures. In this paper, we concentrate on the inuence of instability mode on the templateassisted dewetting process of the thin polymer bilayer.…”
Section: Introductionmentioning
confidence: 99%